An Investigation of High School Preservice Teachers' Self-Efficacy in Teaching Mathematics - Winston Hendricks; Babawande Emmanuel Olawale; Khalid Saddiq (MDPI AG, 2024)
The influential theory proposed by Bandura suggests that teachers with high self-efficacy-those who strongly believe in their abilities-are more likely to effectively enhance learners' performance. Numerous studies have consistently provided substantial evidence supporting this claim. Therefore, it is essential to investigate preservice teachers' self-efficacy in teaching mathematics and their expectations for outcomes. This study aims to ascertain the self-efficacy beliefs of preservice high school teachers regarding mathematics instruction. The Mathematics Teaching Efficacy Beliefs Instrument (MTEBI) survey was completed by 63 participants from a rural institution. This survey was administered after the completion of a Mathematics Methods course but before the onset of the school experience exercise (practicum). The MTEBI consists of 21 items and uses a five-point, forced-choice Likert-like scale to assess participants' perceptions of their effectiveness in teaching mathematics. The survey evaluates two subscales: Personal Knowledge of Mathematics Teaching Efficacy (PMTE) and Expectancy of Mathematics Teaching Outcomes (MTOE). The results on the PMTE subscale showed a mean score of 43.1 and a standard deviation of 6.1, indicating that respondents possess good personal mathematics teaching efficacy. On the MTOE subscale, the participants had a mean score of 31.5 and a standard deviation of 3.72, reflecting a positive anticipation of learners' mathematics learning outcomes. The research also found no statistically significant differences in self-efficacy in teaching mathematics or expectations between the two genders. However, female preservice mathematics teachers reported a notably higher average in teaching self-efficacy and teaching outcome expectancy compared to their male colleagues. Consequently, this study concludes that although female preservice teachers may be more effective than their male counterparts, there is a general need to enhance self-efficacy among all preservice teachers by providing various opportunities, such as increased coursework, field experiences, and peer mentoring.